2001
DOI: 10.1097/00000542-200109000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine 0.2% and Lidocaine 0.5% for Intravenous Regional Anesthesia in Outpatient Surgery

Abstract: Ropivacaine 0.2% may be an alternative to 0.5% lidocaine for intravenous regional anesthesia in the outpatient surgical setting. Longer-lasting analgesia in the immediate postoperative period may be due to a more profound and prolonged tissue binding effect of ropivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 0 publications
4
24
0
4
Order By: Relevance
“…To calculate the required sample size, we took into account results of a previous study by Atanassoff et al [3] with ropivacaine 0.2% and lidocaine 0.5% for IVRA. We wanted to detect a 35% difference in sensory block regression times between groups, accepting a type I error of 0.05 and a type II error of 0.20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the required sample size, we took into account results of a previous study by Atanassoff et al [3] with ropivacaine 0.2% and lidocaine 0.5% for IVRA. We wanted to detect a 35% difference in sensory block regression times between groups, accepting a type I error of 0.05 and a type II error of 0.20.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical use of ropivacaine 0.2% was established for IVRA in one study. Despite the low number of patients, it was reported that ropivacaine yielded satisfactory surgical anesthetic conditions intraoperatively and long-lasting analgesia in the immediate postoperative period [3]. Ropivacaine 0.375% also provided effective anesthesia and superior postoperative analgesia compared with lidocaine 0.5% when forearm IVRA was used [4].…”
Section: Introductionmentioning
confidence: 99%
“…Local anesthetic is then infused into the vein, which subsequently flows retrograde up the limb while diffusing into the tissues while anesthetizing neighboring nerves. 58 The double tourniquet technique is used to provide anesthesia under the area of the cuff to prevent patient discomfort and procedure intolerance related to discomfort from cuff pressure. The anesthetic agent originally described by Bier was procaine, although currently newer agents such as lidocaine and ropivacaine are used more frequently, with ropivacaine possibly providing longer analgesia after cuff deflation.…”
Section: Intravenous Regional Anesthesiamentioning
confidence: 99%
“…The coadministered local anesthetic (0.5% lidocaine or 0.1% to 0.2% ropivacaine) is unlikely to influence results with respect to duration of postoperative analgesia beyond the recovery room period. 257 Complications with IV RA are very uncommon. Seizures have been reported after deflation of the tourniquet with a tourniquet time as long as 60 minutes and with lidocaine at its lowest effective dose (1.5 mg/kg).…”
Section: Intravenous (Bier) Blockmentioning
confidence: 99%